Novabase : equity research - Rosa, Rita Maria Martins Namorado (2015)
The objective of this project is to obtain the Novabase’s price per share at 31st of December 2013. Our main challenge during this dissertation was to define the most suitable valuation model, taking in consideration the specificities of each model and the assumptions inherent in the decision of the model chosen. We decide to explore the Discounted Cash Flow valuation, through Free Cash Flow to the Firm approach and Relative valuation, due to the perspective of growth and characteristics of the industry in which Novabase operates. Despite the fact that similar prices were achieved, we find more appropriate to select the Discounted Cash-Flow valuation, reaching a target price of 3,55€. Once, the price per share of Novabase, at 31st of December 2013 was 2,51€, we recognize an upside of 41% and consequently our recommendation is to Buy.